Susceptibility and virulence profile of Escherichia coli pathotypes isolated from diarrheic and non-diarrheic calves - da Silva Menezes Azola, Juliana [UNESP]; Cardozo, Marita Vedovelli [UNESP]; de Souza Moreira, Bianca; do Nascimento, Gabriel Michelutti [UNESP]; Boriollo, Marcelo Fabiano Gomes; de Ávila, Fernando Antônio [UNESP] (Universidade Estadual de Londrina, 2021)
Neonatal diarrhea is amongst the most frequent diseases affecting calves, leading to damages in milk production. Although Escherichia coli is a commensal microorganism in the gastrointestinal tract, some pathotypes are known to cause high prevalence of diarrhea and food poisoning. The rapidly increasing resistance of bacteria to antimicrobials leads to the research in new, alternative treatment options. The present study aimed at the detection of E. coli pathotypes in newborn diarrheic and non-diarrheic calves, as well as susceptibility tests for antimicrobials and vegetal extracts. Samples were collected from animals located in dairy farms in the state of Minas Gerais, Brazil. The samples were sent for microbiological isolation, genetic identification using PCR and antimicrobial tests. A total of 35 strains from diarrheic animals tested positive for at least one of the virulence genes analyzed: stx1, stx2, eae, bfp and sta. As for the non-diarrheic animals, 9 isolated strains possessed one of or both stx1 and stx2 genes, classifying these non-diarrheic cattle as reservoirs for the STEC pathotype and possible biological vectors of this pathogen. Regarding the susceptibility tests, most isolates displayed resistance to multiple antimicrobial classes. Among the vegetal extracts tested, all isolates tested sensitive to the active ingredient of Salvia officinalis L. (sage). Showcasing an alternative tool to aid in the treatment of pathogenic bacteria.
Perfil de susceptibilidade e virulência de patótipos de Escherichia coli isolados de bezerros diarreicos e nãodiarreicos
Keywords: Colibacillosis; EPEC; ETEC; Salvia officinalis L; STEC